Dioxin-like POPs in national samples from global monitoring plan projects (2017–2019). (June 2023) - Fiedler, Heidelore; Ábalos, Manuela; Parera, Jordi; Abad, Esteban; Lohmann, Nina; Neugebauer, Frank; Rottler, Horst; Horstmann, Michael
Abstract: The global monitoring plan (GMP) established under the Stockholm Convention on Persistent Organic Pollutants (POPs) had defined ambient air, human milk or blood, and water as core matrices to be analyzed and assessed for spatial and temporal distribution. Within projects coordinated by the United Nations Environment Programme (UNEP), developing countries were offered to have other matrices analyzed for dioxin-like POPs (dl-POPs) in experienced laboratories. Subsequently, 185 samples from 27 countries located in Africa, Asia, and Latin America were collected during 2018–2019 and analyzed for polychlorinated dibenzodioxins (PCDD), dibenzofurans (PCDF), and biphenyls (PCB). Using the WHO2005 toxic equivalency approach (TEQ), the amounts of dl-POPs found were low (<1 pg TEQ/g); however, singular samples had higher values; e.g ., egg from Morocco, fish from Argentina or Tunisia; soil and sediment samples. Results showed that the matrix, abiotic or biota, had more impact on the TEQ pattern than the geographic location. Independent of the location and across all samples, dl-PCB in (shell)fish and beef samples had a contribution of 75% to the total TEQ; milk (63%), chicken (52%), and butter (50.2%) more than 50%. Sediment (57% and 32%) and soil (40% and 36%)) samples were dominated by PCDD and PCDF, respectively; therein, dl-PCB had shares of 11% and 24%. Egg samples (N = 27) did not follow the general biota pattern and had 21% of the TEQ from the PCDD, 45% from PCDF, and 34% from dl-PCB; thus, indicating that abiotic matrices such as soil or other material may have an impact. Graphical abstract: Image 1 Highlights: Dioxin-like POPs (dl-POPs, as TEQ) assessed in 185 environmental samples from 27 countries. Distribution of TEQs more governed by type of matrix, abiotic or biota, than geography. Soil and sediment dominated by PCDD or PCDF; most foods of animal origin by dl-PCB. Amounts of dl-POPs found were generally low, although few elevated concentrations encountered. Analytical results being highly selective and sensitive are a prerequisite for comparative assessments.